Perception of hearing protectors by workers that participate in hearing preservation programs: a preliminary study - Gonçalves,Cláudia Giglio de Oliveira (2015)
PURPOSE: To evaluate and compare the workers' perception of comfort and use aspects regarding two types of hearing protectors (shell and earplug), in three units from a lumbering company, with different implantation times for Hearing Preservation Programs.METHODS: This is a cross-sectional study comparing 440 workers' perception of hearing protectors, from three companies in Paraná State (Brazil), with different times for Hearing Preservation Programs. Two closed questionnaires were applied (9 and 10 questions, respectively), with a scale of answers varying from 1 to 5 (Likert's scale) regarding the perception of the comfort of hearing protectors. Then, audiometry results were analyzed.RESULTS: About 17.5% presented audiogram examinations with alterations. With regard to the questionnaire about the comfort perception, the importance of noise attenuation (mean of 4.25) was the most relevant aspect, followed by communication possibility (mean of 4.15). In the protector assessment, Unit A with more Hearing Preservation Program time presented better scores for both the worker's perception of important aspects regarding hearing protector and for the assessment of the used hearing protector. There was a significant difference on communication difficulty with the use of a hearing protector among workers with normal and altered audiograms (p=0.0371). With regard to the global comfort in the comparison of workers using the shell-type hearing protector with those using insert-type hearing protectors, there was no difference (p=0.2264), irrespective of the type of the unit.CONCLUSION: In general, the unit workers presented a good perception of the important aspects about the hearing protection use of both types of hearing protectors.